2018
DOI: 10.1007/s00795-018-0197-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of folate receptor alpha is an independent prognostic factor for outcomes of pancreatic cancer patients

Abstract: Pancreatic cancer has a poor prognosis; hence, novel prognostic markers and effective therapeutic targets should be identified. We aimed to evaluate folate receptor alpha (FR-α) expression in pancreatic cancer and examine its association with clinicopathological features. We utilized tissue samples from 100 primary pancreatic cancer patients who underwent surgery. FR-α was expressed in 37 of 100 cases (37%). The FR-α-positive group (median, 18.8 months) had a significantly poorer prognosis than the FR-α-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…FRα has been found in pancreatic cancer, breast cancer, ovarian cancer, head and neck cancer, lung cancer, bladder cancer, kidney cancer, and colon cancer. Approximately 40% of human cancers overexpress FR [ 34 , 35 ]. A previous study using immunohistochemical analysis showed that in 22 (16%), 73 (52%) and 45 (32%) specimens of 140 PDAC patients, FRα expression intensity was low, moderate, and high, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRα has been found in pancreatic cancer, breast cancer, ovarian cancer, head and neck cancer, lung cancer, bladder cancer, kidney cancer, and colon cancer. Approximately 40% of human cancers overexpress FR [ 34 , 35 ]. A previous study using immunohistochemical analysis showed that in 22 (16%), 73 (52%) and 45 (32%) specimens of 140 PDAC patients, FRα expression intensity was low, moderate, and high, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using immunohistochemical analysis showed that in 22 (16%), 73 (52%) and 45 (32%) specimens of 140 PDAC patients, FRα expression intensity was low, moderate, and high, respectively [ 36 ]. From the database of Encyclopedia of Cancer Cell Lines, at the mRNA level, FRα is highly expressed in pancreatic cancer after breast cancer according to the incidence rate [ 35 ]. Therefore, folate binding is a potential method to target FR-positive tumor tissues for personalized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological FOLR1 (FRα gene) mRNA expression has been reported to be significantly higher in cancers such as mesothelioma, lung, pancreas, ovarian, and colorectal cancers (8)(9)(10)(11). Over-expression histopathological FRα has been reported in adenocarcinoma compared to squamous cell cancers (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological overexpressed FOLR1 in various solid tumors such as breast, ovarian, pancreatic, kidney, and lung cancer, especially NSCLC and high-grade osteosarcoma, was caused by the increased metabolic needs of folates to feed nucleic acid synthesis and cellular growth (5)(6)(7)(8)(9)(10)(11). FOLR1 could be transferred from the localized cell surface to the bloodstream as a soluble form of sFOLR1 (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…PCR is performed to amplify the oligonucleotide bound to the FRα on the CTCs and enhance the detection sensitivity (18). Although FRα was also found to be expressed in tumor tissues of hepatobiliary cancers and pancreatic cancers (32)(33)(34)(35)(36), the clinical utility of FR+CTC in these types of cancer remains to be examined. Hence, in this preliminary study, we aimed to explore the clinical significance of FR+CTC in the differential diagnosis and management of HBPs.…”
Section: Introductionmentioning
confidence: 99%